2019
DOI: 10.1093/ageing/afz162
|View full text |Cite
|
Sign up to set email alerts
|

Estimated societal costs of stroke in the UK based on a discrete event simulation

Abstract: Background there are around 100,000 new stroke cases and over a million people living with its consequences annually in the UK. This has large impacts on health and social care, unpaid carers and lost productivity. We aimed to estimate associated costs. Methods we estimated 2014/2015 annual mean cost per person and aggregate UK cost of stroke for individuals aged ≥40 from a societal perspective. Health and social care costs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 18 publications
1
65
0
2
Order By: Relevance
“…Diringer et al [ 20 ] also found old age, heart problem, male sex, the severity of the stroke, and hospitalisation as predictors of ischemic stroke hospital costs. Similar findings were revealed by a study done in the UK, which found that the mean stroke costs were higher in females aged between 75 and 84 years [ 21 ]. A study conducted in the Netherlands established that hospitalisation costs contributed a larger proportion to total stroke costs and age was significantly associated with stroke costs [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Diringer et al [ 20 ] also found old age, heart problem, male sex, the severity of the stroke, and hospitalisation as predictors of ischemic stroke hospital costs. Similar findings were revealed by a study done in the UK, which found that the mean stroke costs were higher in females aged between 75 and 84 years [ 21 ]. A study conducted in the Netherlands established that hospitalisation costs contributed a larger proportion to total stroke costs and age was significantly associated with stroke costs [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, long term worklessness has been linked to increased risk of depression, suicide, reduced quality of life, cardiovascular disease, and health-harming behaviours (11,12). The societal cost of stroke has been estimated at £26 billion per year, including £8.6 billion for health and social care (13).…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…Conversely, long-term worklessness has been linked to increased risk of depression, suicide, reduced quality of life, cardiovascular disease, and health-harming behaviours [ 11 , 12 ]. The societal cost of stroke has been estimated at £26 billion per year, including £8.6 billion for health and social care [ 13 ]. These costs will likely increase due to strokes occurring at earlier ages, improvements in survival rates, and changes in retirement age provisions [ 1 , 14 ].…”
Section: Introductionmentioning
confidence: 99%